PENGARUH MOTIVASI, BUDAYA ORGANISASI, LINGKUNGAN KERJA, DAN KEPUASAN KERJA TERHADAP KINERJA GURU PADA SMA SE-KOTA JUANG BIREUEN - Saifuddin, Saifuddin (indOmera, 2020)
This research was conducted on high school teachers in Physical Education in Bireuen District, with the aim being a). To find out the magnitude of the influence of the Principal's Leadership on teacher motivation in Physical Education in high schools throughout Bireuen Regency; b). To find out the magnitude of the influence of organizational culture on teacher motivation in Physical Education in high schools throughout Bireuen Regency; c). To find out the magnitude of the effect of financial compensation on the motivation of teachers in Physical Education in high schools throughout Bireuen Regency; and D). To find out the simultaneous influence of the Principal's leadership, organizational culture, and Financial Compensation on the motivation of teachers in Physical Education in the Bireuen District. This research is in the form of quantitative research with a survey of 60 high school Physical Education teachers in the Bireuen Regency, by collecting data through a questionnaire. And the method of data analysis with statistics with the path analysis approach. The results showed that 1). there is an influence of the Principal's Leadership factors on the motivation of high school Physical Education teachers in the Bireuen Regency, which is equal to 35.16%. 2). It also proves the influence of organizational culture factors, namely school culture on the motivation of high school Physical Education teachers in the Bireuen Regency, which is 18.46%. Bireuen, which is 13.81%. 4). The results of the analysis of the value of the coefficient of determination explain that the contribution of the factors of Principal Leadership, Organizational Culture and Financial Compensation to the Physical Education Motivation of 67.4%.